AI-Powered Consumer-Generated Insights for Product Innovation - Asunmonu, Ajoke A. (Darul Yasin Al Sys, 2025)
This research explores how AI-powered consumer-generated insights (CGI) enhance product innovation by analyzing unstructured data from reviews, social media, and visual content. Using natural language processing (NLP) and machine learning (ML), the study examines AI's role in identifying trends, accelerating development, and improving customer-centric design. Through case studies and data analysis, it evaluates AI's effectiveness while addressing challenges like data privacy and algorithmic bias. The findings aim to provide businesses with a practical framework for leveraging AI-driven insights responsibly, offering actionable strategies for faster, more innovative product development.